Trends in Emission Standards and the Implications for Bus Fleet Management: Technology Assessment for Brisbane Transport - Patil, A.; Brown, Kerry (Institute of Electrical and Electronics Engineers ( IEEE, 2008)
Cities around the world have set ambitious emissions reduction targets. They are promoting public transport in order to reduce urban pollution from the transportation sector. Cleaner and less polluting city transit buses are paramount if cities are to attain their ambitious emissions reduction targets, as transit buses are high usage vehicles that operate in heavily congested areas where air quality improvements and reductions in public exposure to harmful air contaminants are critical. Decision to invest in a new bus is based on the cost, technology and emission standards. Frequent changes in the emission standards and evolution of bus technology adds to the uncertainty in decision making. A bus has a life expectancy of about 20 years-during its lifespan if the emission standards change and the bus can no longer satisfy the requirements then it has to be phased out or upgraded to comply with the emission requirements-which costs money and time thus leading to financial and service losses. The objective of a decision maker while investing is to optimize the returns of investments-low costs and lower emissions. This paper will look at the Brisbane Transport as a case study-the aim of this paper is to perform comparative technology assessment and based on that provide recommendations to the Brisbane Transport fleet manager during the selection of new buses, in order to attain the 2026 patronage and emissions targets set by Brisbane.